The interwar world
1 online resource.
Keywords: "The Interwar World collects an international group of over 50 contributors to discuss, analyse and interpret this crucial period in twentieth century history. A comprehensive understanding of the interwar era has been limited by Euro-American approaches and strict adherence to the temporal limits of the world wars. The volume's contributors challenge the era's accepted temporal and geographic framings by privileging global processes and interactions. Each contribution takes a global, thematic approach, integrating world regions into a shared narrative. Three central questions frame the chapters. . First, when was the interwar? Viewed globally, the years 1918 and 1939 are arbitrary limits, and the volume explicitly engages with the artificiality of the temporal framework while closely examining the specific dynamics of the 1920s and 1930s. Second, where was the interwar? Contributors use global history methodologies and training in varied world regions to decenter Euro-American frameworks, engaging directly with the usefulness of the interwar as both an era and an analytical category. Third, how global was the interwar? Authors trace accelerating connections in areas such as public health and mass culture counterbalanced by processes of economic protectionism, exclusive nationalism, and limits to migration. By approaching the era thematically, the volume disaggregates and interrogates the meaning of the 'global' in this era. As a comprehensive guide, this volume offers overviews of key themes of the interwar period for undergraduates, while offering up-to-date historiographical insights for postgraduates and scholars interested in this pivotal period in global history"--